Violências na periferia em tempos pandêmicos: uma perspectiva fenomenológica - Garcia, Carolina Telis (2023)
This research, on a phenomenological approach and a participative, dialogic and interventional character, inaugurates a project from the research group ECOFAM that seeks to discuss the human rights matter, on the violations perspective, especially at educational environments. Currently, the major project involves a set of researches on different subjects, such as inclusive education, corporeity, collaborative education and teenagers’ actions against human rights violations at the outskirts of Sao Paulo. This work talks with the other group projects and intends to understand the experiences of educational equipment’s professionals in relation to those rights violations. Considers, for that, the COVID-9 pandemic context that amplified the inequalities all over the world and had catastrophic effects on the more vulnerable neighborhoods of the country. The general objective of the research is to promote reflections about the violences theme with managers and educators of the institutions. Our specific objective is to create spaces where it is possible to systematically discuss the human rights topic, especially during times of democratic fragility, as well as systematize the experiences. To reach those goals, amid a follow up that lasted over two years, we held reflexive meetings with professionals from a Center for Children and Teenagers (CCA) and two Children Education Centers at Brasilândia, neighborhood of Sao Paulo, for the duration of two months. The meetings were recorded, transcribed and analyzed from the hermeneutics of meanings perspective, and organized on “constellations” named “Children and Teenagers”, “Violences and Justice” and “Confrontations”. The investigation disclosed an appropriation of the outskirts situation about the theme and opened space for the discussion to continue after the pandemic, especially during moments of heated discussions about democracy in the country, like the one we currently go through. The creation of these spaces and the necessity to develop confrontation strategies strengthen the community and open the possibility for future research and interventions